2018
DOI: 10.1136/bmjqs-2018-008659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two behavioural ‘nudging’ interventions on management decisions for low back pain: a randomised vignette-based study in general practitioners

Abstract: Objective‘Nudges’ are subtle cognitive cues thought to influence behaviour. We investigated whether embedding nudges in a general practitioner (GP) clinical decision support display can reduce low-value management decisions .MethodsAustralian GPs completed four clinical vignettes of patients with low back pain. Participants chose from three guideline-concordant and three guideline-discordant (low-value) management options for each vignette, on a computer screen. A 2×2 factorial design randomised participants t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Most of the studies across the two healthcare settings used a pre‐post design. Of the 11 community‐based studies, five (45%) were randomized controlled trials, 38,45‐48 one was cluster‐randomized, 43 one was quasi‐randomized (alternate weeks), 39 and the remaining four (36%) were pre‐post studies40‐42,44: two single‐site and two multi‐site with controls (one with randomized allocation to intervention, the other unclear). Of the 11 hospital‐based studies, seven were single site pre‐post comparisons, 49‐52,54,56,59 one was a two site pre‐post comparison without a control, 53 one was a multi‐site pre‐post with one site non‐randomly allocated to intervention, 57 one was a multi‐site with multiple interventions rolled out at different times (non‐uniformly) across sites, 58 and one was a qualitative study 55 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies across the two healthcare settings used a pre‐post design. Of the 11 community‐based studies, five (45%) were randomized controlled trials, 38,45‐48 one was cluster‐randomized, 43 one was quasi‐randomized (alternate weeks), 39 and the remaining four (36%) were pre‐post studies40‐42,44: two single‐site and two multi‐site with controls (one with randomized allocation to intervention, the other unclear). Of the 11 hospital‐based studies, seven were single site pre‐post comparisons, 49‐52,54,56,59 one was a two site pre‐post comparison without a control, 53 one was a multi‐site pre‐post with one site non‐randomly allocated to intervention, 57 one was a multi‐site with multiple interventions rolled out at different times (non‐uniformly) across sites, 58 and one was a qualitative study 55 .…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the salience studies used defaults and default alerts with reported absolute changes ranging from 4% to 56% (all statistically significant); the largest change was from Malhotra et al 40 who explored the shift in default to prescription of generic versions of medicines. The remaining two studies were simulation studies using partition menus; results for Soon et al 47 were found to be not statistically significant, while Tannenbaum et al 48 showed a reduction in low value antibiotic prescribing by 12%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using participants from survey panels may introduce selection bias as participants are reimbursed in some way for their time. However, reimbursing participants is common and many studies have relied on recruitment agencies [e.g., 26 , 28 ]. Recruiting participants in this manner affords a broad geographical reach increasing the study’s generalisability and tests the “labelling effect” with a large cross-cultural sample.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these studies have been conducted on some limited issues, including smoking and obesity. In behavioral economics, an increasing number of studies has investigated the effect of the nudge approach, especially in the United States and Europe [16,[21], [22], [23]]. However, many of these studies have also focused on smoking and obesity, or when studying the other clinical issues, the study subjects have usually been limited to patients in a certain hospital.…”
Section: Discussionmentioning
confidence: 99%